-4(-6w+v)-6(-6v+w)=

Simple and best practice solution for -4(-6w+v)-6(-6v+w)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-6w+v)-6(-6v+w)= equation:


Simplifying
-4(-6w + v) + -6(-6v + w) = 0

Reorder the terms:
-4(v + -6w) + -6(-6v + w) = 0
(v * -4 + -6w * -4) + -6(-6v + w) = 0
(-4v + 24w) + -6(-6v + w) = 0
-4v + 24w + (-6v * -6 + w * -6) = 0
-4v + 24w + (36v + -6w) = 0

Reorder the terms:
-4v + 36v + 24w + -6w = 0

Combine like terms: -4v + 36v = 32v
32v + 24w + -6w = 0

Combine like terms: 24w + -6w = 18w
32v + 18w = 0

Solving
32v + 18w = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-18w' to each side of the equation.
32v + 18w + -18w = 0 + -18w

Combine like terms: 18w + -18w = 0
32v + 0 = 0 + -18w
32v = 0 + -18w
Remove the zero:
32v = -18w

Divide each side by '32'.
v = -0.5625w

Simplifying
v = -0.5625w

See similar equations:

| -1(-8.3+2.3)= | | V=1xRanswer | | 3f+3=-13 | | -10=-2+1d | | 7-1.7=28.5 | | -4/9=2/9n-2/5 | | 0.4(3.2x+2)-x=2z+1.8 | | 12m=3.96 | | -2(4+2x)=-8+x | | y-5.5=12 | | y+3.4=15 | | 5(4-3x)=4(4-3x) | | 3b+3(3b+2)=-42 | | 5(x+8)-9=9 | | 4/3x3.14x3 | | 4/3x3.14x3cubed | | 32(x-1)+114x+5(x+3)=1607 | | 8-y=11-8 | | 8y^2-26y+21=0 | | 3+c=4 | | 14x+30=6x-40 | | 6x-19+11x-22=180 | | 8v-1=2+10(v+12) | | 11b-8=10+8(b+11) | | 5(4-3x)=10 | | -39/6 | | 8=12y-11y | | 11(b+4)+9=9b-11 | | 7x+20=12x-30 | | 4x^3+3y^2+2z=0 | | (x*x)-(19-x)(19-x)=38 | | 52=4(1+3k) |

Equations solver categories